Assessment of Heavy Elements’ Pollution in Surface Water of Tigris River Between Baghdad and Kut cities, Iraq - Alzaidi, Safa S.; Hassan, Mustafa A. (Iraqi Journal of Science, 2025)
Along the Tigris River is the study area between Baghdad and Kut cities using ten water samples, the current study assesses the pollution caused by heavy metals in water (two samples from drainage water and Eight samples from surface water the water collected from the shore by skimming the surface) on the 4th of November 2023. The heavy element analysis of the study area’s water samples revealed that the water had been polluted with high concentrations of these elements (Pb and Cd). The amounts of heavy metals increased as the river flowed southward. This is related to the reduction in the water level of the Tigris River and the frequent discharge of various pollutants, which have led to an increase in pollution. Organic, and the spread of various chemical pests, an increase in the concentrations of different types of pollutants, whether from hospital pollutants or direct sewage, hospital pollutants are deemed more dangerous due to the potentially pathogenic substances they carry, treatment plant failure to follow wastewater filtration standards, wellbeing, besides rapid population growth rates, The influence of heavy elements found in water on people when exposed to them in high concentrations or over an extended time. However, these metals have no harmful impacts because the concentrations of (Cr, Fe and Cu) in water samples are within both Iraqi and WHO acceptable levels.